РЕЗОНАНСНІ РЕЖИМИ ЛІНІЙНОГО МАГНІТОЕЛЕКТРИЧНОГО ДВИГУНА ВІБРАЦІЙНОЇ ДІЇ - Бондар, Р.П. (Інститут електродинаміки НАН України, Київ, 2022)
The work considers the resonant operation modes of the linear permanent magnet vibratory motor. On the basis of electrical and mechanical equivalent circuits with lumped parameters, expressions for determining the frequencies of mechanical, electrical, energy and power resonances are obtained. The presence of two frequencies of electrical resonance (when the phases of supply voltage and motor current coincide) in a single-mass electromechanical system and four in a two-mass one is substantiated. Representing, according to the electromechanical analogy approach, the back EMF induced due to the movement of the mover by the corresponding voltage drop, expressions for equivalent mechanical impedances are obtained. The dependences of the energy characteristics of the motor (mechanical work and efficiency) on the equivalent circuit parameters are obtained. Based on the expression for the reluctance electromagnetic force, mechanical work is found and its dependence on the phase difference between displacement and current is shown. The phase difference at which the total mechanical work of the motor is maximal is determined. It is shown that the results of the analysis of resonant modes well agree with results of a numerical field study carried out on the basis of the equations of the quasi-stationary magnetic field in the time domain using the finite element method and the moving type of calculation mesh in the mover region. References 12, figures 6, tables 1.